Disclosure Risk and Price Drift - SONG SHIN, HYUN (Journal of Accounting Research, 2006)
ABSTRACT Disclosures play an apparently critical role in the empirical regularity of the short‐run momentum and long‐run reversal in stock returns. Motivated by this evidence, this paper integrates an analysis of disclosures within an asset pricing model to arrive at a framework in which disclosures and asset returns are jointly determined. Disclosures resolve uncertainty, but the increased information flow also raises the risks during the disclosure period. When disclosures and asset returns are modeled jointly, apparently good news is associated with the upward revision of future disclosure risks. The model generates predictions that have the outward appearance of short‐run momentum and long‐run reversal.